Effect of triple superphosphate fertilizer and spraying with licorice root extract In the growth and production of tomato Lycopersicon esculentum Mill - Hussain Alwan Mana (University of Thi-Qar Journal of agricultural research, 2024)
executed Experience during season Agricultural2022-2023 conducted in One HousesPlastic in Al-Fadliyah district, which is located to the south of Dhi Qar Governorate,13 kilometers from the center of the city of Nasiriyah , on plantsTomatoLycopersicom esculentum mill .Classify ,WijdanWith a purpose study impactimpact Fertilizer Super phosphate Triple In concentrations,1.5, 0) 2,5)gm.plant-1 fSpraying With extract Root Sweat licorice (in concentrations)0 , 5 , 10)gm.l-1 on thegrowth The vegetative And syphilis To plant Planted tomatoes inside HousesPlastic.At a fertilization rate of seven Payments And ten Sprinkles from Abstractduring season the growth , And I use design sectors Random Complete(RCBD.)Withthree Duplicates And compared Averages According to a test less difference moralwhen level Prospect0.05And it can summary Results With what Come:1-superiority Moral For plants TransactionB2Fertilizing with fertilizer Superphosphate The trio is focused(2.5Gloom.plants-1)in all adjectives Thoughtful.2-Excellence the focus10gm.l from Extract Sweat licorice in all characteristics thegrowth Study of tomato plants.3-Excellence treatment Interference between concentration2,5gm.plant-1 forfertilizerP2O5And focus10gm.l-1 For extract Sweat licorice in characteristics Lengththe plant,the weight Dry To grow The vegetative,chlorophyll He got it One plant,which I reached the value(200.5poison,205.6Gloom,48.0, SPAD 7.39kg plants-1,)onRelay.exceptrate Phosphorus,rate Materials Solid Melted TSSThe overlapbetweenconcentration 1,5Gloom.plants-1For fertilizer P2O5And focus10Gloom.Liter-1For extract Sweat licoriceSo he gave0.47),6.17) sequentially.